1990
DOI: 10.1080/10934529009375594
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic reduction and clinical improvements in capacitor workers: A feasible method

Abstract: Eleven capacitor workers, occupationally exposed to PCBs and other industrial chemicals, were treated with the detoxification method developed by Hubbard while thirteen co-workers served as controls. The mean pretreatment PCB levels were 28.0 mg/Kg in adipose and 188.0 ;ig/L in serum. At post treatment, PCBs were reduced in serum by 42% (p<0.05) and in adipose by 30% for the six patients without concurrent disease.Patients with concurrent disease had a 10% reduction in adipose levels, while serum levels remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Ideally, a future study would include biomarkers of GWI case status, such as serum autoantibodies [38], or other objective measures such as longer term follow-up changes in hippocampal microstructure [132]. Additionally, biomarkers should be obtained that would represent, in real time, the enhanced detoxification process such as changes in adipose, serum or skin lipids xenobiotic burden [51,52,133,134,135]. Another potential tool is measurement of concentrations of small molecular weight compounds in both serum and sweat before, during and after the regimen [136,137,138].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a future study would include biomarkers of GWI case status, such as serum autoantibodies [38], or other objective measures such as longer term follow-up changes in hippocampal microstructure [132]. Additionally, biomarkers should be obtained that would represent, in real time, the enhanced detoxification process such as changes in adipose, serum or skin lipids xenobiotic burden [51,52,133,134,135]. Another potential tool is measurement of concentrations of small molecular weight compounds in both serum and sweat before, during and after the regimen [136,137,138].…”
Section: Discussionmentioning
confidence: 99%
“…Although further study is required to determine the clinical usefulness of induced depuration through thermal techniques, several studies thus far have confirmed that induced perspiration through sauna therapy can diminish the body burden of assorted bioaccumulated toxicants including persistent polychlorinated biphenyls (PCBs), polybrominated biphenyls, chlorinated pesticides, hexachlorobenzene, and various other toxicants in exposed individuals. [73][74][75][76][77][78][79][80] Another recognized intervention to diminish the body burden of some bioaccumulated toxicants is the Recognized treatment for some types of heavy metal poisoning. 40,41 No evidence in the literature for removal of other types of toxicants Plasmapheresis…”
Section: Interventions To Facilitate Excretion Of Xenobioticsmentioning
confidence: 99%
“…In nearly 40 years of application of this regimen to occupational or environmental exposures, studies have shown statistically significant reductions in human chemical pollutants, including polychlorinated biphenyls (PCBs) and dioxins, 22,23 and subsequent improvements in health. 24,25 Kilburn et al 26 measured improvements in long-term memory, cognitive dysfunction and peripheral neuropathy among firefighters who completed sauna detoxification 6 months after PCB exposure from burning transformers. Tsyb et al 27 described the safety and long-term health improvements in clean-up workers after the Chernobyl disaster.…”
Section: Introductionmentioning
confidence: 99%